Using negative-latency gravitational wave alerts to detect prompt radio bursts from binary neutron star mergers with the Murchison Widefield Array. (21st August 2019) - James, Clancy W; Anderson, Gemma E; Wen, Linqing; Bosveld, Joel; Chu, Qi; Kovalam, Manoj; Slaven-Blair, Teresa J; Williams, Andrew
ABSTRACT: We examine how fast radio burst (FRB)-like signals predicted to be generated during the merger of a binary neutron star (BNS) may be detected in low-frequency radio observations triggered by the aLIGO/Virgo gravitational-wave detectors. The rapidity, directional accuracy, and sensitivity of follow-up observations with the Murchison Widefield Array (MWA) are considered. We show that with current methodology, the rapidity criterion fails for triggered MWA observations above 136 MHz for BNS mergers within the aLIGO/Virgo horizon, for which little dispersive delay is expected. A calculation of the expected reduction in response time by triggering on 'negative latency' alerts from aLIGO/Virgo observations of gravitational waves generated by the BNS inspiral is presented. This allows for observations up to 300 MHz where the radio signal is expected to be stronger. To compensate for the poor positional accuracy expected from these alerts, we propose a new MWA observational mode that is capable of viewing one-quarter of the sky. We show the sensitivity of this mode is sufficient to detect an FRB-like burst from an event similar to GW 170817 if it occurred during the ongoing aLIGO/Virgo third science run (O3).